2010
DOI: 10.3892/ijo_00000621
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling predicts response to temozolomide in malignant gliomas

Abstract: Abstract. Malignant gliomas are highly lethal neoplasms that cannot be cured with currently available therapies. Temozolomide (TMZ) is a recently introduced alkylating agent that has yielded significant benefits and become a key agent in the treatment of high-grade gliomas. However, its survival benefit remains unsatisfactory. Understanding the molecular basis of TMZ sensitivity/resistance is necessary for improving the treatment outcome by devising strategies that are able to circumvent primary drug resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
47
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 41 publications
7
47
0
1
Order By: Relevance
“…Our prior studies have shown that T98G, U-138MG and YH-13 had MGMT mRNA and protein expression, whereas A-172, AM-38, U-87MG and U-251 did not have them (3). Further, a synergistic antitumor effect of combination treatment with IFN-β and TMZ was observed in the TMZ-resistant glioma cells, T98G, due possibly to an attenuation of their MGMT mRNA levels (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our prior studies have shown that T98G, U-138MG and YH-13 had MGMT mRNA and protein expression, whereas A-172, AM-38, U-87MG and U-251 did not have them (3). Further, a synergistic antitumor effect of combination treatment with IFN-β and TMZ was observed in the TMZ-resistant glioma cells, T98G, due possibly to an attenuation of their MGMT mRNA levels (12).…”
Section: Discussionmentioning
confidence: 99%
“…Among the factors that may contribute to the TMZ resistance, O 6 -methylguanine-DNA methyltransferase (MGMT, a protein that removes drug-induced alkylguanine adducts from DNA created by TMZ) is thought to be involved in its principal mechanisms (1,2). In addition, we more recently reported a list of the most highly upregulated and downregulated genes which may be involved in conferring TMZ sensitivity/resistance in malignant gliomas employing a cDNA microarray, and suggested that an elevated level of the MGMT gene is one of the most robust predictors of the TMZ response in malignant glioma cells in vitro (3).…”
Section: Introductionmentioning
confidence: 99%
“…But at present, the underlying mechanism of IDH mutations in tumorigenesis and their prognostic significance is still not clear (39). Further research should be undertaken to open entire new horizon of potential individualized treatment tailored to gene expression profiling and clinical trials for glioma (40).…”
Section: Log-rankmentioning
confidence: 99%
“…Survival-associated genes in gliomas have been reported in various studies (21)(22)(23)(24). Moreover, methylation microarray provides a more general, prognostic, genome-wide methylation profiling, which may have a role in individualized diagnosis and treatment.…”
Section: Discussionmentioning
confidence: 99%